2012
DOI: 10.1136/acupmed-2011-010071
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Human Skin Impedance at Acupuncture Point Pc4 Ximen and pericardium meridian using the four-electrode method

Abstract: Introduction Traditional Chinese medicine offers several theories to explain the mechanism of acupuncture. One of these theories proposes that acupuncture points and meridians have unique electrical properties and their electrical skin impedance is lower than surrounding areas. The aim of this study was to evaluate the differences in electrical skin impedance between PC4 and the pericardium meridian compared with the surrounding areas. Methods Eighteen healthy subjects (10 women) were recruited to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[1][2][3][4][5][6] The AP is reported to be located intramuscularly; if it is within the dermal and subcutaneous tissues, cutaneous wounds and liposuction could extensively destroy the AP. By placing the bipolar electrodes on top of the skin over a purported AP, the current would flow superficially between the electrodes and would probably bypass the area of interest ( figure 1B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The AP is reported to be located intramuscularly; if it is within the dermal and subcutaneous tissues, cutaneous wounds and liposuction could extensively destroy the AP. By placing the bipolar electrodes on top of the skin over a purported AP, the current would flow superficially between the electrodes and would probably bypass the area of interest ( figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that the electrical resistance of the skin over an AP is lower than that over a non-AP, and proposed the finding as indirect evidence of the existence of APs. [1][2][3][4][5][6] However, the precision of skin electrical resistance measurement can be influenced by numerous factors such as dryness of skin, skin thickness, size of the sensing electrode, pressure applied on the electrode, interelectrode distance, room temperature and humidity. 7 Most of the previous studies on AP identification were done with the sensing electrode being stabilised by hand [1][2][3][4][5] ; however, it is likely that small motions of the hand-held electrode could alter the reading of skin resistance and even bias the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more and more attention has been focused on the relationship of acupuncture and circulation [ 11 , 12 , 13 ]. In the meridian study area, the broad consensus in meridian study is a lower impedance along the meridians [ 14 , 15 ]. Usually, the impedance of the skin is proportional to the interstitial fluid volume which comes from microcirculation, so microcirculation might be an index for meridian activation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to evaluate the activation of meridians. Until now, the broad consensus in meridian studies has been the lower impedance along the meridians [2,3]. Usually, the impedance of the skin is proportional to the interstitial fluid volume arising from microcirculation; thus, microcirculation may be an index for meridian activation.…”
Section: Introductionmentioning
confidence: 99%